Immersive technologies as an innovative tool to increase academic success and motivation in higher education - Sviridova, Ekaterina; Yastrebova, Elena; Bakirova, Gulmira; Rebrina, Fayruza (Frontiers in Education, 2023)
The latest techniques and technologies significantly improve the academic performance, engagement, and motivation of students. VR and AR open up numerous opportunities for the educational system. The purpose is to evaluate the effectiveness of using immersive technologies as a tool to increase the level of academic success, involvement, and motivation among students. The research involved a total number of 180 students in two higher educational institutions. This study presupposed using a previously elaborated program for further use in the experimental group. This program was introduced into the study program within the participating universities. The study included three tests to collect the data under the Motivation and Engagement Scale, as well as European Credit Transfer and Accumulation System. The experimental group provided positive indicators during statistical data analysis; thus, it demonstrates the effectiveness of the studied methods. Although the engagement and motivation of students from the experimental group increased, there were no differences in academic achievements between the groups. Therefore, it cannot be argued that immersive technologies have a direct impact on grades, which are the main indicator of success in learning. The new experimental data obtained in this study and the analysis of previous modern experimental studies allowed us to draw relevant conclusions about the expediency and high efficiency of immersive education technologies for teaching university students.